Chimeric lipase for understanding the role of key residues governing pH profiles - Wan Hasan, Wan Atiqah Najiah (2014)
The industrial processes often require enzymes to function under very specific reaction condition. Enzymes which basically are proteins depend greatly on the environmental pH and temperature in order for them to achieve their maximum activity. However, most enzymes from natural source do not meet the industrial processes requirements. Advanced technology and knowledge in protein engineering allow us to modify the natural source enzymes to suit with the industrial condition by changing some components of the protein structure. The study aims to identify key residues modulating the pH profile of lipase by generating chimeric lipases from homologous lipases with different pH profile and to purify and characterize the chimeric lipases. Using the gene shuffling method, fragments of lipase gene from Staphylococcus hyicus lipase and Staphylococcus epidermidis lipase were amplified and purified before being treated with restriction enzyme MseI which cut each lipase at several sites. The digested fragments were purified and assembled using Polymerase Chain Reaction (PCR). Specific primers for each gene were used to reamplify the assembled product. There was full length PCR product with the size of about 1.2 kbp produced when specific primers of Staphylococcus epidermidis lipase were used in the PCR reaction. pTrcHis were used as vector and E. coli TOP10 were used as the host cell to clone and express the chimeric genes. Three chimeric (Chimeric 1, chimeric 2 and chimeric 3) which possessed different optimum pH from the parent lipase were selected for futher investigation after pre-liminary assay screening using p-nitrophenyl butyrate as substrate at pH 4 until 12. Analysis of gene revealed that several mutation sites had occurred in the lipase gene which may lead to the changes of optimum pH. The optimum pH for chimeric 1 (4 mutations),chimeric 2 (3 mutations) and chimeric 3 (2 mutations) were pH6, pH6 and pH8, respectively. The mutation between charged residues to other polar or non polar amino acids caused changes in the electrostatic surface of the protein thus affecting the pH profile of the protein. Site-directed mutagenesis were done for amino acid at point 212 in chimeric 1, 2 and 3 and point 359 in chimeric 3 proved that those amino acids effect the pKa of Histidine 346 which was the active site of the enzyme,possibly contributing to the changes in pH of the enzyme. For the sequence analysis, the chimeric lipases were compared with Staphylococcus epidermidis lipase structure using Yet Another Scientific Artificial Reality Application (YASARA) software. The root mean square deviation (RMSD) values for Staphylococcus epidermidis lipase compared with chimeric 1,2 and 3 were 0.451 Ǻ, 0.528 Ǻ and 0.460 Ǻ,respectively with sequence identity of 97.87%, 96.82% and 97.66%, respectively. The characterization study revealed that chimeric 1 and 2 were able to hydrolyze long carbon chain length substrates up to carbon 18 but chimeric 3 preffered short carbon chain length. The optimum temperature for chimeric 1, 2 and 3 were 35 °C, 30 °C and 45 °C, respectively. As a conclusion, the knowledge of the effect of key residues in changing certain characteristics of an enzyme may be useful for further usage in protein engineering study, such as to create enzymes with specific optimum pH or temperature for various industrial applications.